Manufacturing and Testing of Electrical Pneumatic System Trainers at the Laboratory of Politeknik Piksi Ganesha Indonesia - Hamid Nasrullah; Bahtiar Wilantara; Mohamad Saifudin; Fandi Nugroho (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2022)
The manufacture and testing of the electro pneumatic trainer aims to overcome the limitations of the learning media and determine the effectiveness of the trainer as a learning medium for pneumatic courses. This research uses research and development (R&D) methods. The data analysis technique used was descriptive qualitative analysis technique. The results of the program and functional input testing show that: (1) The push button test as I/O input works well; (2) The functional test of the trainer when given an average pressure of 79.5 psi produces a pneumatic piston speed output of 0.444 m/s. Based on the test results, it can be concluded that the making of the Electro Pneumatic Trainer learning media can function properly. Pembuatan dan Pengujian trainer elektro pneumatik bertujuan untuk mengatasi keterbatasan media pembelajaran serta mengetahui efektifitas trainer sebagai media pembelajaran pada Mata Kuliah Pneumatik. Penelitian ini menggunakan metode penelitian dan pengembangan (R&D). Metode analisis data yang digunakan adalah metode analisis deskriptif kualitatif. Hasil pengujian input program dan fungsional menunjukan bahwa: Pertama, Pengujian push button sebagai input I/O bekerja dengan baik; Kedua, Pengujian fungsional trainer ketika diberi tekanan rata rata 79,5 psi menghasilkan output kecepatan piston pneumatik sebesar 0,444 m/s. Berdasarkan hasil pengujian dapat disimpulkan bahwa pembuatan Trainer Elektro Pneumatik dapat berfungsi dengan baik sesuai prosedur.